A Determination of KIP Kuliah Scholarship Recipients Using the AHP and TOPSIS Method (Case Study: UMKT Student Division) - ARIF RAHMAN HAKIM (School of Computing, Telkom University, 2023)
Student Division Universitas Muhammadiyah Kalimantan Timur manage various scholarship for student,one of them is Kartu Indonesia Pintar Kuliah scholarship, the process include is where UMKT Student Division need to estimate eligible student receiving scholarship based on 4 criteria, the problem may occur is to many scholarship applicant but scholarship quota is limited it’s hard to choose eligible scholarship recipient among student applicant. By using AHP and TOPSIS to determine KIP Kuliah Scholarship Recipients, AHP used to given weight to all criteria, DTKS (0.539), Family Condition (0.086), Family economy (0.093), House Condition (0.282) and topsis used to process all student applicant year 2022 or alternatives, by using ahp and topsis to determine scholarship recipients the model gain 77% accuracy rates.